Effects of L-Glufosinate-ammonium and temperature on reproduction controlled by neuroendocrine system in lizard (Eremias argus). (February 2020) - Zhang, Luyao; Chen, Li; Meng, Zhiyuan; Jia, Ming; Li, Ruisheng; Yan, Sen; Tian, Sinuo; Zhou, Zhiqiang; Diao, Jinling
Abstract: In the context of global warming, an important issue is that many pesticides become more toxic, putting non-target organisms at higher risk of pesticide exposure. Eremias argus (a native Chinese lizard) was selected as animal model in this study. As a kind of poikilothermic vertebrate, E.argus is sensitive to temperature change. The experimental design [(with or without L-Glufosinate-ammonium (L-GLA) pollution × two temperatures (25 and 30 °C)] was used in this study for 90 days to identify the chronic effects of the pesticide–temperature interaction on the lizards' neuroendocrine-regulated reproduction. Survival rate, body weight, clutch characteristics, testicular histopathology, the content of neurotransmitters and related enzyme activity, the level of sex steroid, the expression of Heat shock protein 70 (HSP70), antioxidant system, the accumulation and degradation of L-GLA were examined. Results showed that L-GLA disrupt reproduction of lizards through hypothalamus-pituitary-gonad (HPG) axis. In addition, temperature can not only change the environmental behavior of pesticides, but also alter the physiological characteristics of lizards. Thus, our results emphasized that temperature is an essential abiotic factor that should not be overlooked in ecotoxicological studies. Graphical abstract: Image 1 Highlights: L-GLA exposure disrupt reproduction controlled by neuroendocrine system of lizard. Thermal effects influence the reproduction of lizards. High temperature aggravated the reproductive toxicity of L-GLA to lizards. Thermal effects should be taken into account in the future ecotoxicological studies.